2001
DOI: 10.1053/jhep.2001.23002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cyclooxygenase–2 Promotes the Release of Matrix Metalloproteinase–2 and –9 in Fetal Rat Hepatocytes

Abstract: Treatment of primary cultures of fetal hepatocytes with proinflammatory cytokines, lipopolysaccharide (LPS), and hepatocyte growth factor promoted the expression of cyclooxygenase-2 (COX-2) and the synthesis of high amounts of prostaglandins (PGs). Under these conditions, the active forms of the matrix metalloproteinases-2 and -9 (MMPs) were released to the extracellular medium. This process was inhibited when the synthesis of PGs was suppressed pharmacologically with COX-2 inhibitors. Addition to the cell cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 32 publications
3
65
0
2
Order By: Relevance
“…It is therefore likely that the induced expression of mPGES-1 and attendant augmented production of PGE 2 in myocardiocytes after infarction may contribute to protection of myocardiocytes from injury and reduction of cardiac cell death, whereas PGE 2 produced via the constitutive mPGES-2 may play a role in the maintenance of cardiac homeostasis. Likewise, COX-derived PGs, particularly PGE 2 , play a role in liver regeneration and protection of hepatic tissues from damage (52)(53)(54)(55)(56). Hepatocyte proliferation after partial hepatectomy is significantly reduced when COX-1-deficient mice are treated with a COX-2 inhibitor (55), suggesting the involvement of both COX isoforms in liver regeneration.…”
Section: Mpges-2 and Pge 2 Productionmentioning
confidence: 99%
“…It is therefore likely that the induced expression of mPGES-1 and attendant augmented production of PGE 2 in myocardiocytes after infarction may contribute to protection of myocardiocytes from injury and reduction of cardiac cell death, whereas PGE 2 produced via the constitutive mPGES-2 may play a role in the maintenance of cardiac homeostasis. Likewise, COX-derived PGs, particularly PGE 2 , play a role in liver regeneration and protection of hepatic tissues from damage (52)(53)(54)(55)(56). Hepatocyte proliferation after partial hepatectomy is significantly reduced when COX-1-deficient mice are treated with a COX-2 inhibitor (55), suggesting the involvement of both COX isoforms in liver regeneration.…”
Section: Mpges-2 and Pge 2 Productionmentioning
confidence: 99%
“…This raises the possibility that these compounds alter converging pathways that affect tumour cell apoptosis. COX-2 has been shown to increase the levels of MMP-2, -9, and -14, while NSAIDS and COX-2 inhibitors have been reported to alter the levels of MMP-1, -2, -3, -9 (Ito et al, 1995;Takahashi et al, 1997Takahashi et al, , 1999Attiga et al, 2000;McLaren et al, 2000;Callejas et al, 2001;Jiang et al, 2001). Recent reports have shown that NSAIDs inhibit MMP expression and activation through both COX-2-dependent and independent mechanisms such as through modulation of gene transcription via the ERK/Sp1 signalling pathway or through induction of the membraneanchored MMP inhibitor RECK (Pan et al, 2001;Liu et al, 2002;Pan and Hung, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is now recognized that the antiinflammatory and analgesic actions of nonsteroidal antiinflammatory drugs are largely attributable to inhibition of COX-2 isoenzyme. COX-2 and prostaglandin E 2 are known to induce production of the inflammatory cytokine IL-6 (11 ) and promote the release and activation of MMPs (12 ). Recent studies have shown that expression of COX-2 has also been specifically linked to cardiovascular disease.…”
mentioning
confidence: 99%
“…COX-2-mediated eicosanoid production by activated macrophages may promote atherosclerosis through several mechanisms, including activation of chemotaxis, increased vascular permeability, propagation of the inflammatory cytokine cascade, stimulation of macrophage and smooth muscle cell migration, and stimulation of chemotaxis of human monocytes by LDL (9,11,12,15,20,21 ). It has been reported that COX-2 is also correlated with endothelial dysfunction and oxidative stress, which promote the progress of atherosclerotic inflammation.…”
mentioning
confidence: 99%